Integrated BIM-Based Structural Analysis of a Government Residential Building in Jakarta - Daffa Mahardika; Dedy Rutama; Arief Subagyo (Universitas Medan Area, 2026)
Building Information Modeling (BIM) has increasingly been adopted in government building projects to improve coordination, design accuracy, and structural analysis. However, the integrated application of BIM for both superstructure and substructure evaluation of high-rise government residential buildings remains insufficiently documented. This study evaluates Building A of the Ministry of Finance's State Flats in Jakarta using an integrated BIM-based structural analysis workflow. A case-study approach was employed using Autodesk Revit 2025 for three-dimensional structural modeling, Autodesk Robot Structural Analysis Professional 2025 for static and dynamic structural analysis, and MIDAS GTS NX for foundation and settlement analysis. Structural loading and seismic performance were evaluated according to applicable Indonesian standards. The results showed that the structural model achieved mass participation exceeding 90% in the principal directions, with 97.7% in the X-direction and 99.22% in the Y-direction. The maximum inter-story drift was 35.82 mm, which was below the allowable limit of 108 mm. The special moment-resisting frame also satisfied the minimum contribution requirement within the dual structural system. The 500 mm diameter driven-pile foundation provided adequate axial and lateral capacity, while the maximum long-term settlement was 3 cm, below the allowable limit of 3.5 cm. The integrated BIM workflow successfully supported structural and geotechnical evaluation and provides a replicable approach for BIM-based analysis of high-rise government buildings.